Anibal Quijano: socialization of power as a central issue of socialism - Montoya Rojas, Rodrigo (2019)
By reviewing the academic and political biography of Anibal Quijano, this article reflects around the socialization of power, one of the Peruvian thinker’s proposals, during his second intellectual stage. It begins with his formation, to highlight his initial adherence to Marxism, his sociological production, his commitment and political militancy through the Socialist Revolutionary Movement, the creation of Sociedad y Política magazine, inter alia. This goes hand in hand with two key events in the socio-historical Peruvian process: the emergence of Villa El Salvador and the formation of the Left Revolutionary Alliance. Events to which Quijano’s attention was no stranger.